Desarrollo de un sistema de mesa de ayuda para el control de incidencias del departamento de Tecnología de la ESPAM-MFL - Cagua Intriago, Gabriela Maidanet (2018)
The elaboration of this work was carried out with the objective of developing a help desk application that controls the incidents of the technology department at ESPAM-MFL. The agile development methodology SCRUM was applied, using the software architecture pattern (MVC) in the integrated development environment (IDE) Visual Studio 2013 under the object-oriented programming language C # and the SQL Server 2008 database manager; in addition, the Razor view engine with HTML5, CSS3 and JavaScript was used. In order to establish the functional requirements of the system, which were documented by the IEEE830 standard, the interview technique was conducted for the Technology Department Coordinator, who made known their requirements and expectations about the application. Likewise, use case diagrams with unified modeling language (UML) were designed, which define the functional structure of the system from the point of view of the user. Through this work, the total unification of the processes carried out by the technology department was achieved.